THE IMPACT OF COVID-19 ON THE INSURANCE INDUSTRY OF BANGLADESH - Haque, Anamul; Mohona, Nishat Taslin; Sultana, Sabrin; Kulsum, Umme (Indian Journal of Finance and Banking, 2021)
This study investigates the impact of Covid-19 on the insurance industry of Bangladesh. We utilize a quarterly panel data of top-performing both life and non-life companies for the duration between Q1:2018 to Q1:2021. We depend on the quantitative method to determine the exact scenario implementing through the fixed effect model. The finding explains that the adverse effect of the pandemic is significant on the quarterly premium income, insurance density, and penetration. A robustness test further justifies the validity of the findings. We discuss the causes behind decline to portraits real scenario of such harsh impact. The sector demands potential measures that ensure a stable situation.JEL Classification Codes: G22, I18, I19.